انتشار السلس البولي الليلي عند الأطفال - خوري, مها; شريتح, أحمد; اسماعيل, إيمان (Latakia University Journal -Medical Sciences Series, 2019)
Objective: Nocturnal enuresis is a common problem among children of all ages, and it is a source of stress for both of parents and the child. In this study we aim to determine the prevalence rate of nocturnal enuresis and its related factors. Methods: An observational descriptive cross-sectional study. The study included 830 children aged 5-13 years undertaken at the outpatient pediatric clinic of the Tishreen University Hospital in Latakia between" 2017-2018. A special questionnaire for the study was filled out by the doctor by asking the parents. Results: The prevalence rate of nocturnal enuresis in this study was 23.60%(196 of the 830 children).Primary nocturnal enuresis was(69.90%) vs. Secondary nocturnal enuresis was(30.10%),and monosymptomatic nocturnal enuresis was(61.74%) vs. Non- monosymptomatic nocturnal enuresis was(38.26%).The nocturnal enuresis was associated with the age of the child(p-Value=0.002),positive family history of nocturnal enuresis(p-Value=0.001),low education level of parents (p-Value=0.0001),while there is no association with gender (p-Value=0.7). . Half of the affected children have not received neither behavioral nor medical treatment Conclusions: A quarter of all children of both gender and of all ages suffers from nocturnal enuresis, which makes it a widespread disease in society. Half of the affected children have not received neither behavioral nor medical treatment ,which indicates the parent′s lack of awareness of this disease. This study has shown a strong associated between nocturnal enuresis and the children′s family history, young age and their parents′ low level low of education. أهمية وهدف البحث: يعتبر السلس البولي الليلي من المشاكل الشائعة عند الأطفال بمختلف الأعمار والتي تشكل مصدرا مستمرا للقلق لكل من الأهل والطفل .تهدف هذه الدراسة لتحديد انتشار السلس البولي الليلي وتحديد بعض العوامل المرتبطة بحدوثه. طرق البحث: تم أجراء دراسة رصدية وصفية مقطعية عرضانية لجميع الأطفال المراجعين للعيادة العامة في مستشفى تشرين الجامعي من الذين تراوحت أعمارهم بين 5-13سنة من تاريخ(04-2017) ولغاية (04-2018) حيث بلغ عدد الأطفال المشمولين في الدراسة 830طفلا, تم أخذ المعلومات عن الطفل عن طريق سؤال الأهل وتعبئة الاستبيان الخاص بالدراسة من قبل الطبيب. النتائج: كان السلس البولي الليلي موجودا لدى 196طفلا من مجمل عينة الدراسة أي ما يعادل نسبة 23.60%,كانت نسبة السلس البولي البدئي (69.90%) مقابل الثانوي (30.10%), كما شكل السلس البولي الليلي وحيد العرض (61.74%) مقابل السلس البولي متعدد الأعراض(38.26%).ارتبط حدوث السلس البولي الليلي في دراستنا بعمر الطفل الصغير(p-Value=0.002) ووجود قصة عائلية ايجابية(p-Value=0.001) والمستوى التعليمي المنخفض للأبوين(p-Value=0.0001), بينما لم يكن لجنس الطفل أي أثر على حدوث السلس البولي الليلي (p-Value=0.7).إن نصف الأطفال المصابين لم يتم إجراء استشارة طبية لهم لعلاج حالة السلس البولي الليلي لديهم الاستنتاجات: أظهرت الدراسة أن ربع الأطفال من كلا الجنسين ومن مختلف الأعمار يعانون من السلس البولي الليلي, مما يجعل السلس البولي الليلي مرض منتشر في المجتمع ومشكلة صحة عامة مقلقة. نصف الأطفال المصابين لم تتم معالجة الحالة لديهم سواء كعلاج سلوكي أو دوائي مما يوحي بقلة الوعي حول هذه الحالة المرضية من قبل الأهل . أظهرت هذه الدراسة أيضا ارتباط وثيق بين حدوث السلس البولي الليلي ووجود سوابق عائلية للسلس البولي الليلي والمستوى التعليمي المنخفض للأبوين والعمر الصغير.